PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS SPARKOL VIDEOSCRIBE PADA TEMA 7 SUB TEMA 2 SISWA KELAS IV SD NEGERI 030355 PARRATUSAN - Eva Betty Simanjuntak; Astria Hospital Tampubolon (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to produce sparkol videoscribe-based animated video learning media, to determine the feasibility of sparkol videoscribe-based animated video learning media and to determine the effectiveness of using Sparkol videoscribe-based animated video learning media on Theme 7 Sub-theme 2 Grade IV Students of SD Negeri 030355 Parratusan. This research and development was carried out using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation) with the research subjects being fourth grade students of SD Negeri 030355 Parratusan. The results of this development research are appropriate and effective learning media to use. The final result by a material expert is 95% or in the “Very Eligible” category. Furthermore, the final result from the media expert is 100% included in the "Very feasible" category, then the results obtained from the fourth grade teacher are 97% and are included in the "very Eligible" category and at the time of product testing the average score obtained from students is 94 %. Then based on the results of the pretest and posttest obtained an increase in student learning outcomes with the achievement of KKM. Keywords: Development, Learning Media, Video Animation, Sparkol Videoscribe.